STRATEGI BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DALAM MENINGKATKAN JUMLAH PESERTA JAMINAN KESEHATAN NASIONAL (JKN) DI KABUPATEN SIAK - Ari Pepbrian; Harapan Tua R.F.S (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Social Security Administrator (BPJS) is a Public Legal Entity that is tasked with organizing National Health Insurance for all Indonesians. National Health Insurance (JKN) is a Government program that aims to provide a comprehensive guarantee of health insurance for all Indonesians to be able to live healthy, productive and prosperous lives. The low participation of National Health Insurance is recognized by BPJS. Because the number of participants is still low, a strategy is needed to increase the participation of the National Health Insurance. Theoretical concepts used is SWOT Analysis in the Strategic Management book by Sondang P. Siagian to determine the right strategy to overcome the problem. This study uses qualitative methods with descriptive data assessment. In collecting data, researcher used three types of activities in qualitative data analysis, namely : data reduction, data model, drawing/verification conclusions. The results of the study show that the Social Security Administrator (BPJS) in its entirety has not been able to increase number of participants the National Health Insurance in Siak Regency. Factors that influence are the economic condition and awareness of the society. It is expected that the BPJS of Siak Regency will apply more strategies to attract the interest of the society.Keywords: Strategy, Health Social Security, Program